Обработка семян пшеницы сорта "Навруз" плазмой барьерного разряда при атмосферном давлении - Ходжаев, Абдулло Тоирович (Перспективы развития фундаментальных наук. Т. 2 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25–28 апреля 2023 г.)
Currently, to improve the growth and development of agricultural plants, different physical methods of influencing factors on seeds before sowing are widely used. The work shows that pre-sowing treatment of seeds with thermal neutrons improved the realization of genetic information and contributes to the enhancement of physical and biochemical processes. At the initial stages of seed germination in the results of the study it was found that the irradiation of wheat seeds by neutrons primarily affects the germination energy and complete germination. In this regard, we investigated the effect of barrier discharge at atmospheric pressure in three variants. Experiments showed that the barrier discharge will give a positive effect leading to changes in physical and morphological properties of wheat of its functional group NH, as well as growth processes plant development is closely related to the activity and amount of the key enzyme of photosynthesis CO2.